2017
DOI: 10.1021/jacs.6b11013
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Insights into the Multi-Antioxidative Mechanisms of Melanin Nanoparticles and Their Application To Protect Brain from Injury in Ischemic Stroke

Abstract: Nanotechnology-mediated antioxidative therapy is emerging as a novel strategy for treating a myriad of important diseases through scavenging excessive reactive oxygen and nitrogen species (RONS), a mechanism critical in disease development and progression. However, similar to antioxidative enzymes, currently studied nano-antioxidants have demonstrated scavenging activity to specific RONS, and sufficient antioxidative effects against multiple RONS generated in diseases remain elusive. Here we propose to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
392
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 443 publications
(422 citation statements)
references
References 60 publications
(110 reference statements)
15
392
0
2
Order By: Relevance
“…Our results do suggest that, depending on the intensity of the oxidative reaction, chemically-distinct, dark-or light-colored MN-like pigments could be generated depending on the type of precursor that is present. Such physically and chemically distinct MN materials could find different applications 7,16,[43][44][45][46] or possess different cell-biological properties [47][48][49][50][51][52] In addition, our results suggest that the absence of a dark color does not necessarily mean the absence of MN-like materials which may have implications for the evaluation of histological or fossil specimens. [53][54] …”
Section: 323uv-vis Spectroscopy and Fluorescence Emissionmentioning
confidence: 90%
“…Our results do suggest that, depending on the intensity of the oxidative reaction, chemically-distinct, dark-or light-colored MN-like pigments could be generated depending on the type of precursor that is present. Such physically and chemically distinct MN materials could find different applications 7,16,[43][44][45][46] or possess different cell-biological properties [47][48][49][50][51][52] In addition, our results suggest that the absence of a dark color does not necessarily mean the absence of MN-like materials which may have implications for the evaluation of histological or fossil specimens. [53][54] …”
Section: 323uv-vis Spectroscopy and Fluorescence Emissionmentioning
confidence: 90%
“…[10][11][12][13][14][15] However, low molecular weight antioxidants (for instance NXY-059) have historically not translated well in the treatment of stroke patients. [19] They also showed in a rat model of ischemic stroke that MeNPs reduce brain superoxide levels and infarct volume. [16][17][18] For example, Liu and colleagues have demonstrated that melanin NPs (MeNPs) scavenge multiple reactive oxygen and nitrogen species (RONS), suppress RONS-induced inflammation, and are neuroprotective in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] It reacts with proteins, DNA, or lipids, to achieve irreversible cellular components damage and dysfunction in cell metabolism and even cell apoptosis. [24][25][26] The accumulated H 2 O 2 further transforms into highly cytotoxic hydroxyl radical (OH•) to significantly aggravate the oxidative damage and enhance PDT anticancer efficiency. [24][25][26] The accumulated H 2 O 2 further transforms into highly cytotoxic hydroxyl radical (OH•) to significantly aggravate the oxidative damage and enhance PDT anticancer efficiency.…”
Section: Doi: 101002/advs201900530mentioning
confidence: 99%